Investigation on the Ultraviolet-Visible Luminescence of Ce3+ Activated K2CaP2O7 Phosphor. (1st January 2016) - Hou, Dejian; Li, Jin-Yan; Pan, Xixiang; Ye, Xinyu; Fu, Junxiang; Li, Ruining
Abstract : In this work, a series of Ce 3+ ions activated K2 CaP2 O7 phosphors were prepared through a solid-state reaction method. The luminescence spectra in the ultraviolet-visible range as well as the decay curves were studied. Ce 3+ ions enter one Ca 2+ site in the host, the two emission bands are at 347 nm and 369 nm. The five 4f–5d excitation bands and the centroid shift of Ce 3+ were determined at low temperature. The critical energy transfer distance and the luminescence thermal quenching properties were also discussed.